Two-nozzle hydrodynamic focusing. (17th February 2015) - Psychogios, Ioannis; Hatziavramidis, Dimitrios
Abstract: Hydrodynamic focusing is a technique used in flow cytometers for sorting and counting cells. This technique may be also applied for sorting and counting cell clusters in other flow devices and has been recently applied to a device of encapsulation of pancreatic cell islets. Existing models of hydrodynamic focusing assume that sample and sheath fluids have identical densities and viscosities even though the sample fluid is loaded with cells. A computational model of hydrodynamic focusing has been developed which allows sample and sheath fluids to have different densities and viscosities and to be miscible or immiscible. Simulations using this model confirm that the most important parameter governing hydrodynamic focusing is the sheath-to-sample-fluid velocity ratio. Highlights: A model of two-nozzle hydrodynamic focusing for pancreatic cell islet encapsulation is presented. Model allows co-flowing miscible or immiscible fluids of different properties and interfacial dynamics. Simulations show that as sheath-to-sample-fluid-velocity ratio increases, focusing width decreases.